Microfluidic chip-based one-step fabrication of an artificial photosystem i for photocatalytic cofactor regeneration - Huang, X.; Liu, Jian; Yang, Q.; Liu, Y.; Zhu, Y.; Li, T.; Tsang, Y.; Zhang, X. (Royal Society of Chemistry, 2016)
We propose herein, a one-step method to assemble the immobilized artificial photosystem I (IAPSI) in a microfluidic chip, which integrated a preformed graphitic carbon nitride photocatalyst (g-C3N4) and electron mediator (M) in one chip and mimicked the characteristics of photosystem I. The simultaneous assembly of g-C3N4and M could efficiently regenerate NADH from NAD+under visible light irradiation, which verified the effectiveness of the assembly method. The in situ assembly method was thought to outperform traditional methods in several aspects in terms of facile synthesis, promotion of the combination of g-C3N4and M through p-p stacking and an enhanced coenzyme regeneration rate. For comparison, we used the bulk g-C3N4-slurry and the few-layer g-C3N4-slurry system as the control to regenerate the photocatalytic cofactor/coenzyme NADH, and measured the required times of 305 s and 30 s, respectively, to accomplish 63% NAD+conversion. In contrast, our IAPSI microreactor takes only 13 s, faster than the other two by factors of 23 and 2.3 times. Therefore, we assert that the simple, yet highly efficient nature of this technique can act as an important method for artificial photosynthesis, particularly in the photocatalytic cofactor recycling systems for the production of various valuable molecules.